Review of the U.S. Global Change Research Program's Update to the Strategic Plan Document - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The Update to the Strategic Plan (USP) is a supplement to the Ten-Year Strategic Plan of the U.S. Global Change Research Program (USGCRP) completed in 2012. The Strategic Plan sets out a research program guiding thirteen federal agencies in accord with the Global Change Research Act of 1990. This report reviews whether USGCRP’s efforts to achieve its goals and objectives, as documented in the USP, are adequate and responsive to the Nation’s needs, whether the priorities for continued or increased emphasis are appropriate, and if the written document communicates effectively, all within a context of the history and trajectory of the Program.
Keywords: Environment and Environmental Studies

New Tools for Environmental Protection: Education, Information, and Voluntary Measures - National Research Council (The National Academies Press, 2002)
Many people believe that environmental regulation has passed a point of diminishing returns: the quick fixes have been achieved and the main sources of pollution are shifting from large "point sources" to more diffuse sources that are more difficult and expensive to regulate. The political climate has also changed in the United States since the 1970s in ways that provide impetus to seek alternatives to regulation. This book examines the potential of some of these "new tools" that emphasize education, information, and voluntary measures. Contributors summarize what we know about the effectiveness of these tools, both individually and in combination with regulatory and economic policy instruments. They also extract practical lessons from this knowledge and consider what is needed to make these tools more effective.The book will be of interest to environmental policy practitioners and to researchers and students concerned with applying social and behavioral sciences knowledge to improve environmental quality.
Keywords: Environment and Environmental Studies

Characterizing Risk in Climate Change Assessments: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The U.S. Global Change Research Program (USGCRP) was established in 1990 to "assist the Nation and the world to understand, assess, predict, and respond to human-induced and natural processes of global change."1 A key responsibility for the program is to conduct National Climate Assessments (NCAs) every 4 years.2 These assessments are intended to inform the nation about "observed changes in climate, the current status of the climate, and anticipated trends for the future." The USGCRP hopes that government entities from federal agencies to small municipalities, citizens, communities, and businesses will rely on these assessments of climate- related risks for planning and decision-making. The third NCA (NCA3) was published in 2014 and work on the fourth is beginning. The USGCRP asked the Board on Environmental Change and Society of the National Academies of Sciences, Engineering, and Medicine to conduct a workshop to explore ways to frame the NCA4 and subsequent NCA reports in terms of risks to society. The workshop was intended to collect experienced views on how to characterize and communicate information about climate-related hazards, risks, and opportunities that will support decision makers in their efforts to reduce greenhouse gas emissions, reduce vulnerability to likely changes in climate, and increase resilience to those changes. Characterizing Risk in Climate Change Assessments summarizes the presentations and discussions from the workshop.
Keywords: Environment and Environmental Studies

Modeling Mobile-Source Emissions - Transportation Research Board; National Research Council (The National Academies Press, 2000)
The Mobile Source Emissions Factor (MOBILE) model is a computer model developed by the U.S. Environmental Protection Agency (EPA) for estimating emissions from on-road motor vehicles. MOBILE is used in air-quality planning and regulation for estimating emissions of carbon monoxide (CO), volatile organic compounds (VOCs), and nitrogen oxides (NOx) and for predicting the effects of emissions-reduction programs. Because of its important role in air-quality management, the accuracy of MOBILE is critical. Possible consequences of inaccurately characterizing motor-vehicle emissions include the implementation of insufficient controls that endanger the environment and public health or the implementation of ineffective policies that impose excessive control costs. Billions of dollars per year in transportation funding are linked to air-quality attainment plans, which rely on estimates of mobile-source emissions. Transportation infrastructure decisions are also affected by emissions estimates from MOBILE. In response to a request from Congress, the National Research Council established the Committee to Review EPA's Mobile Source Emissions Factor (MOBILE) Model in October 1998. The committee was charged to evaluate MOBILE and to develop recommendations for improving the model.
Keywords: Environment and Environmental Studies

Managing Coal Combustion Residues in Mines - National Research Council (The National Academies Press, 2006)
Burning coal in electric utility plants produces, in addition to power, residues that contain constituents which may be harmful to the environment. The management of large volumes of coal combustion residues (CCRs) is a challenge for utilities, because they must either place the CCRs in landfills, surface impoundments, or mines, or find alternative uses for the material. This study focuses on the placement of CCRs in active and abandoned coal mines. The committee believes that placement of CCRs in mines as part of the reclamation process may be a viable option for the disposal of this material as long as the placement is properly planned and carried out in a manner that avoids significant adverse environmental and health impacts. This report discusses a variety of steps that are involved in planning and managing the use of CCRs as minefills, including an integrated process of CCR characterization and site characterization, management and engineering design of placement activities, and design and implementation of monitoring to reduce the risk of contamination moving from the mine site to the ambient environment. Enforceable federal standards are needed for the disposal of CCRs in minefills to ensure that states have adequate, explicit authority and that they implement minimum safeguards.
Keywords: Environment and Environmental Studies

Double-Hull Tanker Legislation: An Assessment of the Oil Pollution Act of 1990 (The National Academies Press, 1998)
The passage of the Oil Pollution Act of 1990 (OPA 90) by Congress and subsequent modifications of international maritime regulations resulted in a far-reaching change in the design of tank vessels. Double-hull rather than single-hull tankers are now the industry standard, and nearly all ships in the world maritime oil transportation fleet are expected to have double hulls by about 2020. This book assesses the impact of the double hull and related provisions of OPA 90 on ship safety, protection of the marine environment, and the economic viability and operational makeup of the maritime oil transportation industry. The influence of international conventions on tank vessel design and operation is addressed. Owners and operators of domestic and international tank vessel fleets, shipyard operators, marine architects, classification societies, environmentalists, and state and federal regulators will find this book useful.
Keywords: Environment and Environmental Studies

Tank Waste Retrieval, Processing, and On-site Disposal at Three Department of Energy Sites: Final Report - National Research Council (The National Academies Press, 2006)
DOE Tank Waste: How clean is clean enough? The U.S. Congress asked the National Academies to evaluate the Department of Energy’s (DOE’s) plans for cleaning up defense-related radioactive wastes stored in underground tanks at three sites: the Hanford Site in Washington State, the Savannah River Site in South Carolina, and the Idaho National Laboratory. DOE plans to remove the waste from the tanks, separate out high-level radioactive waste to be shipped to an off-site geological repository, and dispose of the remaining lower-activity waste onsite. The report concludes that DOE’s overall plan is workable, but some important challenges must be overcome—including the removal of residual waste from some tanks, especially at Hanford and Savannah River. The report recommends that DOE pursue a more risk-informed, consistent, participatory, and transparent for making decisions about how much waste to retrieve from tanks and how much to dispose of onsite. The report offers several other detailed recommendations to improve the technical soundness of DOE's tank cleanup plans.
Keywords: Environment and Environmental Studies

Research Priorities for Airborne Particulate Matter: I. Immediate Priorities and a Long-Range Research Portfolio - National Research Council (The National Academies Press, 1998)
New National Ambient Air Quality Standards for airborne particles smaller than 2.5 micrometers, called PM2.5, were issued by the U.S. Environmental Protection Agency (EPA) amidst scientific uncertainty and controversy. In response to a request from Congress, Research Priorities for Airborne Particulate Matter, the first of four books in a series, offers a conceptual framework for an integrated national program of particulate-matter research, identifies the 10 most critical research needs linked to key policy-related scientific uncertainties, and describes the recommended timing and estimated costs of such research. The committee concludes that EPA should devote more resources to investigating the relationships between fixed-site outdoor monitoring data and actual human breathing-zone exposures to ambient particulate matter and to identifying the most biologically important constituents and characteristics of particulate matter through toxicological studies. The recommended research activities are critical to determining actual exposures of human subpopulations most susceptible to harm from the most hazardous constituents of particulate matter. Future research will be an investment in public health and a means to ensure that resources spent on control technology and regulatory compliance will have a reasonable probability of success.
Keywords: Environment and Environmental Studies

Review of the EPA's Economic Analysis of Final Water Quality Standards for Nutrients for Lakes and Flowing Waters in Florida - National Research Council (The National Academies Press, 2012)
The Environmental Protection Agency's estimate of the costs associated with implementing numeric nutrient criteria in Florida's waterways was significantly lower than many stakeholders expected. This discrepancy was due, in part, to the fact that the Environmental Protection Agency's analysis considered only the incremental cost of reducing nutrients in waters it considered "newly impaired" as a result of the new criteria-not the total cost of improving water quality in Florida. The incremental approach is appropriate for this type of assessment, but the Environmental Protection Agency's cost analysis would have been more accurate if it better described the differences between the new numeric criteria rule and the narrative rule it would replace, and how the differences affect the costs of implementing nutrient reductions over time, instead of at a fixed time point. Such an analysis would have more accurately described which pollutant sources, for example municipal wastewater treatment plants or agricultural operations, would bear the costs over time under the different rules and would have better illuminated the uncertainties in making such cost estimates.
Keywords: Environment and Environmental Studies

Evaluating Chemical and Other Agent Exposures for Reproductive and Developmental Toxicity - National Research Council (The National Academies Press, 2001)
The United States Navy has been concerned for some time with protecting its military and civilian personnel from reproductive and developmental hazards in the workplace. As part of its efforts to reduce or eliminate exposure of Naval personnel and their families to reproductive and developmental toxicants, the Navy requested that the National Research Council (NRC) recommend an approach that can be used to evaluate chemicals and physical agents for their potential to cause reproductive and developmental toxicity. The NRC assigned this project to the Committee on Toxicology, which convened the Subcommittee on Reproductive and Developmental Toxicology, to prepare this report. In this report, the subcommittee recommends an approach for evaluating agents for potential reproductive and developmental toxicity and demonstrates how that approach can be used by the Navy. This report has been reviewed in draft form by individuals chosen for their diverse perspectives and technical expertise, in accordance with procedures approved by the NRC's Report Review Committee. The purpose of this independent review is to provide candid and critical comments that will assist the institution in making its published report as sound as possible and to ensure that the report meets institutional standards for objectivity, evidence, and responsiveness to the study charge. The review comments and draft manuscript remain confidential to protect the integrity of the deliberative process. We wish to thank the following individuals for their review of this report: James Chen (National Center for Toxicological Research), George Daston (Procter and Gamble Company), Jerry Heindel (National Institute of Environmental Health Sciences), Grace Lemasters (University of Cincinnati), and John Young (National Center for Toxicological Research).
Keywords: Environment and Environmental Studies

Health Effects of Exposure to Radon: BEIR VI - National Research Council (The National Academies Press, 1999)
Radon progeny—the decay products of radon gas—are a well-recognized cause of lung cancer in miners working underground. When radon was found to be a ubiquitous indoor air pollutant, however, it raised a more widespread alarm for public health. To develop appropriate public policy for indoor radon, decisionmakers need a characterization of the risk of radon exposure across the range of exposures people actually receive. In response, the BEIR VI committee has developed a mathematical model for the lung cancer risk associated with radon, incorporating the latest information from epidemiology and scientific studies. In this book the committee provides a fresh assessment of exposure-dose relationships. The volume discusses key issues—such as the weight of biological evidence and extrapolation from radon-exposed miners to the larger population—in estimating the risk posed by indoor radon. It also addresses such uncertainties as the combined effects of smoking and radon and the impact of the rate of exposure. The committee considered the entire body of evidence on radon and lung cancer, integrating findings from epidemiological studies with evidence from animal experiments and other lines of laboratory investigation. The conclusions will be important to policymakers and environmental advocates, while the technical findings will be of interest to environmental scientists and engineers.
Keywords: Environment and Environmental Studies

Public Participation in Environmental Assessment and Decision Making - National Research Council (The National Academies Press, 2008)
Federal agencies have taken steps to include the public in a wide range of environmental decisions. Although some form of public participation is often required by law, agencies usually have broad discretion about the extent of that involvement. Approaches vary widely, from holding public information-gathering meetings to forming advisory groups to actively including citizens in making and implementing decisions. Proponents of public participation argue that those who must live with the outcome of an environmental decision should have some influence on it. Critics maintain that public participation slows decision making and can lower its quality by including people unfamiliar with the science involved. This book concludes that, when done correctly, public participation improves the quality of federal agencies' decisions about the environment. Well-managed public involvement also increases the legitimacy of decisions in the eyes of those affected by them, which makes it more likely that the decisions will be implemented effectively. This book recommends that agencies recognize public participation as valuable to their objectives, not just as a formality required by the law. It details principles and approaches agencies can use to successfully involve the public.
Keywords: Environment and Environmental Studies

Emergency and Continuous Exposure Guidance Levels for Selected Submarine Contaminants: Volume 1 - National Research Council (The National Academies Press, 2007)
U.S. Navy personnel who work on submarines are in an enclosed and isolated environment for days or weeks at a time when at sea. Unlike a typical work environment, they are potentially exposed to air contaminants 24 hours a day. To protect workers from potential adverse health effects due to those conditions, the U.S. Navy has established exposure guidance levels for a number of contaminants. The Navy asked a subcommittee of the National Research Council (NRC) to review, and develop when necessary, exposure guidance levels for 10 contaminants. Overall, the subcommittee found the values proposed by the Navy to be suitable for protecting human health. For a few chemicals, the committee proposed levels that were lower than those proposed by the Navy. In conducting its evaluation, the subcommittee found that there is little exposure data available on the submarine environment and echoed a previous recommendation from an earlier NRC report to conduct monitoring that would provide a complete analysis of submarine air and data on exposure of personnel to contaminants.
Keywords: Environment and Environmental Studies

The Congestion Mitigation and Air Quality Improvement Program: Assessing 10 Years of Experience -- Special Report 264 - Transportation Research Board (The National Academies Press, 2002)
TRB Special Report 264 - Congestion Mitigation and Air Quality Improvement Program: Assessing 10 Years of Experience recommends that Congress retain the sole federal surface transportation program that funds projects to reduce pollution and traffic congestion in areas that must comply with national air quality standards. The Congestion Mitigation and Air Quality Improvement (CMAQ) program was enacted as part of the surface transportation legislation authorized in 1991 to provide support for projects that would aid local efforts to meet the strict new federal deadlines imposed by the Clean Air Act Amendments (CAAA) of 1990. CMAQ was included in the reauthorization of surface transportation legislation in 1998 for another 6 years, and funding for this period was set at $8.1 billion. In the 1998 legislation, Congress also requested an evaluation of the effectiveness of the program and the cost-effectiveness of the projects funded by the program. CMAQ funds are focused primarily on the transportation control measures (TCMs) contained in the 1990 CAAA (with the exception of vehicle scrappage programs, which have not been permitted). TCMs are strategies whose primary purpose is to lessen the pollutants emitted by motor vehicles by decreasing highway travel (for example, bicycle, pedestrian, and some transit projects) and to encourage more efficient facility use (for example, projects focused on ridesharing and on traffic flow improvements, such as signal timing). In addition, CMAQ funds may be used for projects that reduce vehicle emissions directly, such as through vehicle inspection and maintenance programs and purchase of alternative-fueled transit vehicles. In the spirit of the legislation that originally authorized the program, decisions about project selection are made at the local level, usually by or through the local metropolitan planning organization. After reviewing the limited information available about these types of projects, the committee that evaluated the CMAQ program concluded that, when compared on the sole criterion of tons of emissions reduced per dollar spent, strategies aimed directly at emissions reductions—such as emissions and fuel standards for new vehicles, well-structured inspection and maintenance programs, and vehicle scrappage programs—are more cost-effective than the typical CMAQ TCMs, which tend to depend on changes in behavior. A few behaviorally based TCMs, however, such as pricing and regional ridesharing, compare favorably with vehicle- and fuel-based strategies. The committee recommended that the CMAQ program be continued, in part because it is a "funded" rather than an "unfunded" mandate. The committee also called for a focus of future projects on reductions in emissions with the largest public health consequences and for improved evaluation of project effectiveness. Special Report 264 Summary
Keywords: Environment and Environmental Studies

Offshore Situation Room: Enhancing Resilience to Offshore Oil Disasters in the Gulf of Mexico: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
More than a decade after the Deepwater Horizon disaster, the Gulf Research Program convened a diverse group of 60 experts in a virtual event to inform its efforts to enhance resilience to future offshore oil disasters in the Gulf of Mexico region. The event, Offshore Situation Room, took place over three half-days during June 15-17, 2021, and had four main objectives: 1) develop a concise, prioritized list of questions that need to be addressed to support successful prevention, response, and recovery that would minimize the impacts of an offshore oil disaster; 2) provide a collaborative atmosphere where participants can share ideas, capabilities, and information, and build a community dedicated to the successful prevention of, response to, and recovery from an offshore oil spill disaster; 3) explore capabilities for and impediments to prevention, response, recovery, and understanding impacts of an offshore oil disaster in the Gulf of Mexico; and 4) highlight how changes in policy, response, resilience, and restoration efforts may affect outcomes of a major offshore incident. This publication summarizes the presentations and discussion of the event.
Keywords: Environment and Environmental Studies

Behavioral Measures of Neurotoxicity - National Research Council (The National Academies Press, 1990)
Exposure to toxic chemicals—in the workplace and at home—is increasing every day. Human behavior can be affected by such exposure and can give important clues that a person or population is in danger. If we can understand the mechanisms of these changes, we can develop better ways of testing for toxic chemical exposure and, most important, better prevention programs. This volume explores the emerging field of neurobehavioral toxicology and the potential of behavior studies as a noninvasive and economical means for risk assessment and monitoring. Pioneers in this field explore its promise for detecting environmental toxins, protecting us from exposure, and treating those who are exposed.
Keywords: Environment and Environmental Studies

Global Environmental Change: Understanding the Human Dimensions - National Research Council (The National Academies Press, 1992)
Global environmental change often seems to be the most carefully examined issue of our time. Yet understanding the human side—human causes of and responses to environmental change—has not yet received sustained attention. Global Environmental Change offers a strategy for combining the efforts of natural and social scientists to better understand how our actions influence global change and how global change influences us. The volume is accessible to the nonscientist and provides a wide range of examples and case studies. It explores how the attitudes and actions of individuals, governments, and organizations intertwine to leave their mark on the health of the planet. The book focuses on establishing a framework for this new field of study, identifying problems that must be overcome if we are to deepen our understanding of the human dimensions of global change, presenting conclusions and recommendations.
Keywords: Environment and Environmental Studies

Toward Environmental Justice: Research, Education, and Health Policy Needs - Institute of Medicine (The National Academies Press, 1999)
Driven by community-based organizations and supported by a growing body of literature, the environmental justice movement contends that poor and minority populations are burdened with more than their share of toxic waste, pesticide runoff, and other hazardous byproducts of our modern economic life. Is environmental degradation worse in poor and minority communities? Do these communities suffer more adverse health effects as a result? The committee addresses these questions and explores how current fragmentation in health policy could be replaced with greater coordination among federal, state, and local parties. The book is highlighted with case studies from five locations where the committee traveled to hear citizen and researcher testimony. It offers detailed examinations in these areas: Identifying environmental hazards and assessing risk for populations of varying ethnic, social, and economic backgrounds, and the need for methodologies that uniquely suit the populations at risk. Identifying basic, clinical, and occupational research needs and meeting challenges to research on minorities. Expanding environmental education from an ecological focus to a public health focus for all levels of health professionals. Legal and ethical aspects of environmental health issues. The book makes recommendations to decision-makers in the areas of public health, research, and education of health professionals and outlines health policy considerations.
Keywords: Environment and Environmental Studies

Integrating Landscape Approaches and Multi-Resource Analysis into Natural Resource Management: Summary of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The responsible management of natural resources for present-day needs and future generations requires integrated approaches that are place-based, embrace systems thinking, and incorporate the social, economic, and environmental considerations of sustainability. Landscape-scale analysis takes this holistic view by focusing on the spatial scales most appropriate for the resource types and values being managed. Landscape-scale analysis involves assessing landscape features in relation to a group of influencing factors such as land use change, hydrologic changes or other disturbances, topography, and historical vegetation conditions. As such, different types of data and multiple disciplines may be required for landscape analysis, depending on the question of interest and scale of analysis. Multi-resource analysis (MRA) is an approach to landscape-scale analysis that integrates information among multiple natural resources, including ecosystem services, and is designed to evaluate impacts and tradeoffs between development and conservation at landscape scales to inform public resource managers. This approach implicitly addresses social, economic, and ecological functional relationships; for example, actions to realize the benefits of one type of natural resource (e.g., minerals, oil, and gas) may influence behavior and potential benefits related to other types of natural resources (e.g., recreational opportunities). In June 2015, the National Academies of Sciences, Engineering, and Medicine convened a workshop on using landscape-based approaches and MRA to better inform federal decision making for the sustainable management of natural resources. Participants discussed knowledge gaps and priority areas for research and presentations of case studies of approaches that have been used to effectively integrate landscape-based approaches and MRA into practice. This report summarizes the presentations and discussions from the workshop.
Keywords: Environment and Environmental Studies

The Behavioral and Social Sciences: Achievements and Opportunities - National Research Council (The National Academies Press, 1988)
This volume explores the scientific frontiers and leading edges of research across the fields of anthropology, economics, political science, psychology, sociology, history, business, education, geography, law, and psychiatry, as well as the newer, more specialized areas of artificial intelligence, child development, cognitive science, communications, demography, linguistics, and management and decision science. It includes recommendations concerning new resources, facilities, and programs that may be needed over the next several years to ensure rapid progress and provide a high level of returns to basic research.
Keywords: Environment and Environmental Studies